Compatibility And Degradability Of Kenaf-Filled Linear Low Density Polyethylene Polyvinyl Alcohol Composites - PANG, AI LING (2018)
The research on natural fibres polymer composites are rapidly growing due to an increasing demand on environmentally friendly polymer products with reasonable price. The on-going efforts are focused on the improvement in overall properties of these composites. In this research work, linear low-density polyethylene (LLDPE)/poly (vinyl alcohol) (PVOH) blend were utilized as polymer matrices with a fixed composition at 60/40 (wt. %), whereas kenaf bast fiber (KNF) was used as filler. The effect of filler loading, as well as various chemical treatments on the natural filler towards the processing characteristic, tensile, structural, morphological, thermal and biodegradability properties of LLDPE/PVOH/KNF composites were explored. LLDPE/PVOH/KNF composites containing different KNF loadings (i.e. 0, 10, 20, 30 and 40 phr) were prepared by means of melt-mixing and compression moulding. It was found that with increasing KNF loading, the processing torque, tensile modulus, thermal stability and water absorption of composites were increased. Nevertheless, tensile strength and elongation at break of composites were found declined. This indicated weak interfacial adhesion between LLDPE/PVOH matrices and KNF, as revealed by SEM studies. Natural weathering and soil burial has affected the properties of LLDPE/PVOH/KNF composites, as displayed by the deterioration in tensile properties, damage of exposed surfaces, and higher percentage of weight loss. Results from FTIR spectra further confirmed the occurrence of degradation with appearance of intense carbonyl peaks. The existence of chemical treatments of KNF has enhanced the tensile, morphological and thermal properties, as well as reduced the water absorption of LLDPE/PVOH/KNF composites. The chemical treatment of KNF was further confirmed by FTIR spectroscopy. Based on the results, it was found that addition of 3- (trimethoxysilyl)propyl methacrylate (TMS) treated KNF into LLDPE/PVOH matrices has increased the processing torque, tensile strength, tensile modulus, thermal stability and reduced the water absorption of the composites. This was evidenced by the enhanced interfacial adhesion between TMS-treated KNF and LLDPE/PVOH matrices in SEM analysis. Addition of treated KNF with eco-friendy coupling agent (EFCA), chromium (III) sulfate and lysine into LLDPE/PVOH matrices were found respectively increased the processing torque, tensile properties, thermal stability and reduced the water absorption of composites. Results from SEM analysis revealed an improvement in the interfacial adhesion between treated KNF and LLDPE/PVOH matrices. FTIR results also confirmed that chemical bonds were formed between coupling agents and KNF, subsequently provide linkages between KNF and LLDPE/PVOH matrices.